Kinerja Call Center 108 Dalam Memberikan Informasi Di PT Infomedia Bandung - Dewi Untari; Muhammad Faizal (Universitas Bina Sarana Informatika, 2019)
The purpose of this study was to study the achievement of 108 call centers in providing information. This study uses a type of research Descriptive research using qualitative data collected rather than data, passing data that can be obtained from observations, field records and interviews. the results of the study regarding Call Center Performance 108 in providing information. Call Center 108 has an important role for its users to get telephone numbers throughout Indonesia and information about Telkom services, because Call Center 108 is the only Telkom telephone number information service provider in Indonesia. the call center agent's 108 performance is quite good, this can be seen from the average agent performance table, but there are still some agents who have not yet obtained the predetermined value which is 100 that has been determined in the service parameters of PT. Infomedia Nusantara.